2021
DOI: 10.1001/jamanetworkopen.2021.32271
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Changes in Grams of Sugar Sold After the Implementation of the Seattle Sweetened Beverage Tax

Abstract: IMPORTANCEAdults and children routinely exceed recommended intake amounts of added sugars established by dietary guidelines. Taxes are used as a policy tool to reduce demand for sugarsweetened beverages (SSBs) given consumption-related adverse health outcomes but may induce substitution to other sources of added sugars. OBJECTIVE To examine the extent to which changes in grams of sugar sold from taxed beverages may be offset by changes in grams of sugar sold from untaxed beverages, sweets, and stand-alone suga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 32 publications
3
24
1
1
Order By: Relevance
“…The evidence from twelve studies (with 15 independent effect estimates) suggests taxes on SSBs reduced consumers purchasing such beverages ( µ = −0.18 [95%CI : −0.29 to −0.07] ; p = 0.001; Figure 5). We examined the studentized residuals and found that one study (26) had a value larger than 2.94 and may be a potential outlier in the context of this model. Our results remain significant when we removed this effect from the analysis ( µ = −0.07 [95%CI : −0.12 to 0.03] ; p = 0.001).…”
Section: Taxes On Beverages May Reduce Purchases Of Taxed Beveragesmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence from twelve studies (with 15 independent effect estimates) suggests taxes on SSBs reduced consumers purchasing such beverages ( µ = −0.18 [95%CI : −0.29 to −0.07] ; p = 0.001; Figure 5). We examined the studentized residuals and found that one study (26) had a value larger than 2.94 and may be a potential outlier in the context of this model. Our results remain significant when we removed this effect from the analysis ( µ = −0.07 [95%CI : −0.12 to 0.03] ; p = 0.001).…”
Section: Taxes On Beverages May Reduce Purchases Of Taxed Beveragesmentioning
confidence: 99%
“…Based on evidence from 11 studies, our metaanalysis suggests there is no effect of taxes on SSBs on the purchasing of untaxed beverages ( µ = 0.02 (95%CI : −0.06 to 0.02) ; p = 0.33; Figure 6). Studies considered calories purchased (17), grams of sugar purchased (26), volume purchased (15,20,29,30,36,(39)(40)(41)(42). There was moderate heterogeneity in results (Q (10) = 19.61, p = 0.03, τ 2 = 0.00, I 2 = 49.01%).…”
Section: Taxes On Sugar-sweetened Beverages Have No Effect On Purchas...mentioning
confidence: 99%
“…In this context, QEM can provide evidence of the tax impact on: (i) firm response (product range and possible reformulations, tax pass-through and price); 72–76 and (ii) consumer response (including substitution patterns to other beverages and foods, at-home and out-of-home) 77 and, potentially sugar and other nutrient intakes. 78 , 79 One further key input needed in SM that QEM can provide are heterogeneous policy responses across firms and population sub-groups (e.g. CATE estimates).…”
Section: Discussionmentioning
confidence: 99%
“…Another strand of this literature looks at what people consume instead of SSBs when they become more expensive (Aguilar et al, 2021;Duffey et al, 2010;Finkelstein et al, 2013;Fletcher et al, 2010), with mostly ambiguous results which suggest that people may still be making other unhealthy choices. One important exception to this is Powell et al (2021) which finds that overall grams of sugar sold went down by 19% in Seattle following the implementation of its tax, suggesting that SSB taxes could in fact lead to permanent reductions in added sugars being purchased. Noting the importance of measuring changes in self-reported consumption in addition to purchasing behavior, others have used repeated cross-sectional surveys to assess whether people are drinking fewer SSBs.…”
mentioning
confidence: 99%
“…Notably, it is free of the measurement error and response-bias which can plague survey data. It can also be useful for studying tax avoidance behavior when data is available from stores on either side of a taxed border (Bollinger & Sexton, 2018;Powell & Leider, 2020a, 2020bSeiler et al, 2021), and it can be used to study what people are consuming instead of SSB's when taxes cause increases in their prices (Aguilar et al, 2021;Finkelstein et al, 2013;Powell et al, 2021). One important issue with most scanner data, however, is that it tracks purchases made by a household head, and it cannot specify which family member is consuming which items.…”
mentioning
confidence: 99%